Lexicons Analysis of Movements in Rejang Sari Dance - Putu Eka Dambayana S; Wahyuni, Ni Ketut Mery (Universitas Pendidikan Ganesha, 2022)
Rejang Sari dance is a Balinese sacred dance which is only performed by the female dancers as a form of religious offering to God and its manifestations. Currently, in the midst of many people learning this dance, there are cultural changes and social influences that affect the lexicons related this dance. That condition has an impact on decreasing the use and knowledge of Balinese language, especially the lexicons used in the dance. Most of the dance practitioners do not know what the lexicons are actually meant in it. This study aimed to discover and analyze the lexicons exist in movements of the dance, including their cultural meaning. This study using descriptive qualitative approach as the design, the research data were obtained through observation and interview technique with three informants. The results show that there are 37 lexicons exist in the dance and those lexicons are categorized into: dance stages (5 lexicons: pepeson, kawitan, pengawak, pengecet, pekaad), head movement (4 lexicons: nganggut, nengadah, toleh kanan, toleh kiri), neck movement (1 lexicon: ngileg/ngotag leher), hand movement (19 lexicons: ngukel, nyempuri/ngiting, ngembat kanan, ngembat kiri, nyalud, ngayun kanan, ngayun kiri, nyeblak sampul kanan, nyeblak sampul kiri, piles kanan, piles kiri, nyogok kanan, nyogok kiri, agem kanan, agem kiri, jeriring, gerak sekar, mentang kanan, mentang kiri), body movement (2 lexicons: ngenjet & ngegol), and leg movement (6 lexicons: ngumbang, ngumbang gelantik nuut papah, nyerigsig/nyigcig, metanjek, tapak sirang pada, gejug).